Penyelesaian Sengketa Wanprestasi Akibat Keterlambatan Pelaksanaan Perjanjian Kontsruksi Bangunan - Martin Putri Nur Jannah; Dewi Nurul Musjtar (UIR Press, 2019)
Development is an effort to create prosperity and welfare for the people. A development work cannot be separated from the construction contract. In its implementation, In its implementation, many construction service providers, both service users and contractors, did not carry out their achievements as specified in the contract. The Building Construction Contracts on the construction of the Grhatama Pustaka Library Building in the Special Region of Yogyakarta is considered as a default. The purpose of this study is to determine the dispute resolution for delays in the achievement of performance on the implementation of the Building Construction Contracts based on Decision Number: 87/Pdt.G/2013/PN.Bantul. This study uses a normative juridical approach using legislation and jurisprudence (court decisions). The results showed that dispute resolution for delays in fulfilling litigation performance through the Bantul District Court with Results of Decisions obliged service providers to submit building construction work to service users in a proper and good condition and were obliged to pay compensation and interest to service users.